Nominal Quantification in Kipsigis - Landman, Meredith (My University, 2019)
n this paper, I examine the syntax and semantics of nominal quantification in Kipsigis, a Nilotic language spoken in western Kenya. I present a compositional analysis of quantificational nominals and discuss how the Kipsigis patterns relate to previous crosslinguistic work on quantification.
Keywords: Kipsigis; nominal quantification; Nilotic language; Kenya